2023
DOI: 10.32471/exp-oncology.2312-8852.vol-41-no-3.13597
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic cancer therapy modulates monocyte-macrophage cell functions: how it impacts on treatment outcomes

Abstract: Summary. Macrophages are important effectors of innate immunity and the key component of the tumor microenvironment strongly influencing cancer disease outcome and efficiency of cancer therapy. Moreover, recent data have shown that monocytes as macrophage precursors can impact on tumor ability to progression. It’s well known that although tumor-associated macrophages consist of diverse populations, in general, they have tumor-supporting activity. To change tumor-supporting state of tumor-associated macrophages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In a recent review, Patysheva et al indicated that the response of monocyte/macrophage cells to treatment by cytostatic agents is probably realized due to a change in the function of these cells. Moreover, the authors suggest that chemotherapeutic treatment might also affect the functional polarization of monocytes and macrophages and modulate their epigenetic profile and activate recruitment from the bone marrow and migration to the tumor site (Patysheva et al 2019). In agreement with other studies, ~ 40% depletion of the ability of monocyte/macrophage cells to proliferate after treatment by 5-FU has been observed (Fig.…”
Section: Biological Studiesmentioning
confidence: 99%
“…In a recent review, Patysheva et al indicated that the response of monocyte/macrophage cells to treatment by cytostatic agents is probably realized due to a change in the function of these cells. Moreover, the authors suggest that chemotherapeutic treatment might also affect the functional polarization of monocytes and macrophages and modulate their epigenetic profile and activate recruitment from the bone marrow and migration to the tumor site (Patysheva et al 2019). In agreement with other studies, ~ 40% depletion of the ability of monocyte/macrophage cells to proliferate after treatment by 5-FU has been observed (Fig.…”
Section: Biological Studiesmentioning
confidence: 99%
“…Chemotherapeutic agents can affect monocyte subpopulations in circulation blood ( 160 , 188 , 189 ). In breast cancer cohort, the amount of CD3-CD14+CD16- monocytes was increased during 5 cycles of doxorubicin, dramatically decreased after 5 th cycle, but then has reсovered after following 3 cycles of paclitaxel treatment ( 183 ).…”
Section: Effects Of Treatment On Circulating Monocytesmentioning
confidence: 99%